Transmission of multidrug-resistant Campylobacter jejuni to children from different sources in Pakistan. (March 2020) - Noreen, Zobia; Siddiqui, Fariha; Javed, Sundus; Wren, Brendan W.; Bokhari, Habib
Highlights: There is a high prevalence of among diarrhoeal paediatric patients. The majority of Campylobacter jejuni (> 90%) isolates were multidrug-resistant. 7.3% of isolates were metallo-β-lactamase producers. Livestock-associated isolates had a high MAR index as compared with non-livestock. Abstract: Objectives: Due to the rapid emergence of multidrug-resistant isolates, Campylobacter jejuni ( C. jejuni ) has been classified as a member of the priority pathogens group. This study aimed to determine the prevalence, antibiotic resistance patterns and source tracking of clinical C. jejuni isolates from paediatric diarrhoeal patients in Pakistan. Methods: A total of 150 stool samples from children were processed for the presence of C. jejuni using culture, biochemical tests and species-specific PCR. Antibiotic susceptibility of the isolates was determined by the disc diffusion method, and metallo-β-lactamase (MBL) producers were detected using gene-specific PCR. Source tracking was performed using source-predictive PCR. Results: C. jejuni was present in 54.6% of the processed samples. More than 80% of the isolated strains were resistant to seven of 12 tested antibiotics. High levels of susceptibility were observed against imipenem (12.2%) and TGC (9.7%). Six isolates (7.3%) were MBL producers and positive for at least one of the five MBL genes. Source tracking showed that 57.3% of the isolates belonged to livestock-associated clusters (C1–C6) and 42.8% were assigned to non-livestock/environmental clusters (C7–C9). Isolates belonging to livestock clusters had a high Multiple Antibiotic Resistance (MAR) index ( P < 0.001) as compared with non-livestock. Conclusion: A high prevalence of multidrug-resistant C. jejuni among paediatric diarrhoeal patients was observed. Moreover, the association of these isolates to livestock clades suggests transmission to human populations via the food chain. The presence of imipenem-resistant MBL-producing C. jejuni can lead to serious public health concerns.